The Impact of Greenwashing Towards Brand Trust and Brand Loyalty: A Study of Nike Move to Zero Initiatives - Patricia Diandra; Fitri Aprilianty (Mandalika Journal of Business and Management Studies, 2024)
Green marketing is vital for companies to meet consumer demand for sustainable products. However, greenwashing—where companies falsely claim environmental benefits—poses a significant challenge, particularly in the fashion industry, by eroding consumer trust and undermining genuine sustainability efforts. Nike, a leading brand in athletic apparel and footwear, launched the Move to Zero initiative aiming for zero waste and zero carbon emissions by 2025. Despite this, some consumers suspect greenwashing, leading to scepticism about Nike’s sustainability claims. A notable lawsuit has suggested that Nike misled consumers about the actual environmental impact of its products, potentially harming brand trust and loyalty. This study investigates the impact of greenwashing on brand trust and loyalty in the context of Nike's initiative. Using a quantitative approach, surveys were distributed to Nike customers in Indonesia aware of the Move to Zero initiative. Data analysis using descriptive statistics and the PLS-SEM method revealed significant concerns about greenwashing. Many respondents believe Nike's sustainability claims are more marketing than genuine commitment, are sceptical about the effectiveness of the initiatives, and feel Nike needs more transparency about its sustainability practices and impact. The PLS-SEM analysis showed that greenwashing significantly tarnishes the green brand image, leading to a diminished perception of Nike’s environmental efforts. A strong green brand image positively influences brand trust, but overall trust scores were low due to perceived greenwashing. Brand trust positively impacts brand satisfaction, which in turn influences brand loyalty. However, dissatisfaction due to perceived greenwashing lowers both trust and loyalty. The PLS-SEM analysis also indicated significant variance in brand trust and loyalty explained by preceding variables. The findings highlight the importance of transparency and authenticity in green marketing to foster brand loyalty. This research offers valuable insights for Nike and other brands on enhancing trust and loyalty through genuine sustainability efforts and avoiding greenwashing.